2015
DOI: 10.1016/j.dadm.2014.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal subfield surface deformity in nonsemantic primary progressive aphasia

Abstract: Background Alzheimer neuropathology (AD) is found in almost half of patients with non-semantic primary progressive aphasia (PPA). This study examined hippocampal abnormalities in PPA to determine similarities to those described in amnestic AD. Methods In 37 PPA patients and 32 healthy controls, we generated hippocampal subfield surface maps from structural MRIs and administered a face memory test. We analyzed group and hemisphere differences for surface shape measures and their relationship with test scores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 57 publications
(106 reference statements)
0
18
0
Order By: Relevance
“…Several investigators have reported that the shapes of brain structures can provide an additional dimension (structural morphology) when quantifying alterations in cognitive ability in AD/MCI patients ( Qiu et al, 2008 ; Tang et al, 2015 , 2016 ). However, hippocampal shape abnormalities ( Apostolova et al, 2006 ; Christensen et al, 2015 ) and texture features ( Li et al, 2010 ; Zhang J. et al, 2012 ) have been reported to be associated with individual memory performance. Hence, the present study provides additional clues regarding the morphological alterations that occur in the hippocampus in AD.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have reported that the shapes of brain structures can provide an additional dimension (structural morphology) when quantifying alterations in cognitive ability in AD/MCI patients ( Qiu et al, 2008 ; Tang et al, 2015 , 2016 ). However, hippocampal shape abnormalities ( Apostolova et al, 2006 ; Christensen et al, 2015 ) and texture features ( Li et al, 2010 ; Zhang J. et al, 2012 ) have been reported to be associated with individual memory performance. Hence, the present study provides additional clues regarding the morphological alterations that occur in the hippocampus in AD.…”
Section: Discussionmentioning
confidence: 99%
“…Yushkevich et al [15, 16] proposed a multi-atlas segmentation algorithm using a library of manually labeled T1 and T2 scans, whose output was refined by a machine learning bias correction strategy. Wang et al [17, 18] employed a surface-based atlas approach. Our group, in previous work, used a probabilistic atlas to produce segmentations with a Bayesian inference algorithm within a generative framework.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, other studies found no differences in hippocampal volume in PPA compared to healthy controls (van de Pol, et al, 2006), and found no relationship between medial temporal volume and memory performance across subtypes and related syndromes (Irish, et al, 2015; Mansoor, et al, 2015). Another study including a mix of agrammatic and logopenic non-semantic PPA patients found that even in the absence of overt deficits in memory when compared to controls, subtle hippocampal shape surface deformities were related to memory performance (Christensen, et al, 2015). Future longitudinal studies will show whether the memory perturbations in PPA are exclusively caused by damage within the language network or whether they also relate to the eventual spread of pathology to the hippocampal complex.…”
Section: Discussionmentioning
confidence: 99%